Efecto de la densidad de semilla sobre la calidad de plántulas en almácigos de 4 líneas promisorias de arroz (Oryza sp.) a nivel de campo. - Macías Castillo, Manolo Nataniel (2024)
Rice (Oryza sativa L.) is the second most consumed cereal worldwide, in Ecuador the province of Guayas and Los Ríos are the main provinces with the largest total harvested area, for seedlings a density of 50-60 kg/ha is used this study established the effect of seed density on seedling quality in seedlings of 4 promising rice lines (Oryza sp.) at the field level the trial received the respective integrated management of the seedbed the evaluated variables were: Vigor, plant height (cm), number of leaves, stem diameter (mm) and number of seedlings/area for data processing, ANAVA was applied using completely randomized block design with factorial arrangement of a (5 promising lines/variety - control) x B (5 seed densities: Kg/150 m2 seedbed). In relation to the results, all densities showed morphological differences in the seedlings studied densities of 40-45-50 Kg/ha demonstrated seedlings with better quality in the different variables studied regarding the interactions of A x B, the L-38 line at the density of 45 (kg/m2) presented the best plant height, obtaining a value of 23.23 cm; likewise, the L-17 line at the density of 40 kg/ m2 presented the highest number of leaves per plant. Obtaining a value of 4.53 cm on average the interaction of L-17 at a density of 55 (kg/ m2) showed a greater stem thickness, obtaining a value of 0.97 mm, and at the same time the best vigor value was obtained by SFL-11 at a density of 55 kg/ m2 with a value of 2 the L-37 line at the density of 50 (kg/ m2) obtained values of 92 seedlings/area it is recommended to perform tests related to the other phenological stages with the results obtained in this research until production.